The role of secretarial professionals in the fight against corruption in Nigeria - Abe, Sunday; Abe, Sidikat (Journal of Professional Secretaries and Office Administrators, 2017)
Corruption, whichever dimension, has tremendous negative implications for the development and growth of any society. Corruption in the public sector involves the looting and embezzlement of public funds for personal use. Corruption is Nigeria’s biggest challenge. It is clear to every citizen that the level of corruption in the country is high. It is found in every sector of the society (both public and private sectors). The quest for self-preservation has outweighed national interest which brought about lack of national development in Nigeria. The focus of this paper is on the role of secretarial professionals in the fight against corruption. As secretaries are found in every organization, working closely with high and mighty, therefore, their roles in checkmating the excesses of greedy leaders, bosses or employees through good and thorough documentation cannot be overemphasized.